2001
DOI: 10.1038/ng0501-46
|View full text |Cite
|
Sign up to set email alerts
|

First genetic evidence of GABAA receptor dysfunction in epilepsy: a mutation in the γ2-subunit gene

Abstract: Major advances in the identification of genes implicated in idiopathic epilepsy have been made. Generalized epilepsy with febrile seizures plus (GEFS+), benign familial neonatal convulsions and nocturnal frontal lobe epilepsy, three autosomal dominant idiopathic epilepsies, result from mutations affecting voltage-gated sodium and potassium channels, and nicotinic acetylcholine receptors, respectively. Disruption of GABAergic neurotransmission mediated by gamma-aminobutyric acid (GABA) has been implicated in ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
440
3
12

Year Published

2002
2002
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 656 publications
(467 citation statements)
references
References 20 publications
12
440
3
12
Order By: Relevance
“…Nevertheless, this should be interpreted with caution as such difference may be caused by biased sampling or simply, a matter of chance. It is worth noting that only one study of alcohol dependence found an association with an SNP conferring aminoacid changes at the GABA A subunit genes on 5q33, 20 while the rest reported associations with SNPs conferring no amino-acid changes; [17][18][19] we found the reported SNPs conferring amino-acid changes [21][22][23][24] not polymorphic in this study. To further this research, additional SNPs should be identified within this gene cluster and these should be combined using haplotype analysis.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…Nevertheless, this should be interpreted with caution as such difference may be caused by biased sampling or simply, a matter of chance. It is worth noting that only one study of alcohol dependence found an association with an SNP conferring aminoacid changes at the GABA A subunit genes on 5q33, 20 while the rest reported associations with SNPs conferring no amino-acid changes; [17][18][19] we found the reported SNPs conferring amino-acid changes [21][22][23][24] not polymorphic in this study. To further this research, additional SNPs should be identified within this gene cluster and these should be combined using haplotype analysis.…”
Section: Discussioncontrasting
confidence: 46%
“…We examined 11 single-nucleotide polymorphisms (SNPs) located across the GABA A subunit gene cluster on 5q33, including eight previously reported, [17][18][19][20][21][22][23][24] two extracted from the dbSNP of National Center for Biotechnology Information and one found in the 5 0 -untranslated region (5 0 -UTR) of the GABA A g2 subunit gene.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Up to date, at least seven mutations of GABRG2 including missense mutations, nonsense mutations and splice-site mutation have been associated with a broad spectrum of epilepsies. 1,[4][5][6][7][8]14 The N40S mutation identified in this study affects a highly conserved Asn at residue 40 of the mature g2 subunit, thus, the mutation is adjacent to the first one of the two high-affinity benzodiazepine-binding domains of the g2 subunit (Lys-41-Trp-82 in the mature g2 subunit). Wallace et al 15 had suggested that R43Q mutation in the benzodiazepine-binding site can attenuate benzodiazepine sensitivity of GABA A receptor.…”
Section: Discussionmentioning
confidence: 86%
“…[1][2][3][4] A mutation of GABRA1 was found in autosomal dominant juvenile myoclonic epilepsy, a rare inherited idiopathic epilepsy phenotype. 2 Several variants of GABRD were not reported as causes of epilepsy but suggested to associate with susceptibility to genetic epilepsy with febrile seizures plus (GEFS+).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation